Acrolein induces NLRP3 inflammasome-mediated pyroptosis and suppresses migration via ROS-dependent autophagy in vascular endothelial cells. (1st December 2018) - Jiang, Chunteng; Jiang, Liping; Li, Qiannan; Liu, Xiaofang; Zhang, Tianjiao; Dong, Linlin; Liu, Tiehong; Liu, Li; Hu, Guoling; Sun, Xiance; Jiang, Lijie
Highlights: Acrolein induced pyroptosis and suppressed migration in HUVECs. Acrolein-induced　pyroptosis was dependent on the activation of NLRP3 inflammsome. Acrolein-suppressed cell migration was involved in NLRP3 inflammsome and pyroptosis. ROS-dependent autophagy signal pathway was the main way. Collapse of ΔΨm was autophagy dependent and damaged mitochondrion accentuated NLRP3 inflammsome and pyroptosis. Abstract: Acrolein is a common environmental pollutant that has been linked to cardiovascular diseases, such as atherosclerosis (AS). Increasing evidence demonstrates that acrolein impairs the cardiovascular system by targeting vascular endothelial cells, but the underlying mechanisms haven't been completely elucidated. In human umbilical vein endothelial cells (HUVECs), we observed that acrolein treatment induced cell reactive oxygen species (ROS) generation, autophagy, pyroptosis and reduced cell migration. In addition, exposure to acrolein resulted in NLRP3 inflammasome activation as evidenced by cleavage of caspase-1 and downstream mature interleukin (IL)-1β and IL-18 secretion. Knockdown of NLRP3 by small interfering RNA remarkably suppressed acrolein-induced pyroptosis and increased cell migration. Moreover, the scavenging ROS relieved the autophagy, NLRP3 inflammasome activation and pyroptosis. Furthermore, the role of autophagy in the acrolein-medicated pyroptosis and cell migration was investigated. In our study, 3-methyladenine (3-MA), an autophagy inhibitor, aggravated NLRP3 inflammasome activation, pyroptosis and decreased cell migration, rapamycin (Rapa), an autophagy inducer, alleviated aforementioned phenomenon under acrolein stress. Besides, we found damaged mitochondrion accentuated NLRP3 inflammasome and pyroptosis in acrolein-treated cells. In conclusion, it is possible that acrolein induced cell pyroptosis and suppressed cell migration via ROS-dependent autophagy. What's more, NLRP3 inflammasome activation plays a key role in this process.